Pathogenesis of Abdominal Aortic Aneurysms: Role of Nicotine and Nicotinic Acetylcholine Receptors - Li, Zong-Zhuang (Hindawi Publishing Corporation, 2012)
Inflammation, proteolysis, smooth muscle cell apoptosis, and angiogenesis have been implicated in the pathogenesis of abdominal aortic aneurysms (AAAs), although the well-defined initiating mechanism is not fully understood. Matrix metalloproteinases (MMPs) such as MMP-2 and -9 and other proteinases degrading elastin and extracellular matrix are the critical pathogenesis of AAAs. Among the risk factors of AAAs, cigarette smoking is an irrefutable one. Cigarette smoke is practically involved in various aspects of the AAA pathogenesis. Nicotine, a major alkaloid in tobacco leaves and a primary component in cigarette smoke, can stimulate the MMPs expression by vascular SMCs, endothelial cells, and inflammatory cells in vascular wall and induce angiogenesis in the aneurysmal tissues. However, for the inflammatory and apoptotic processes in the pathogenesis of AAAs, nicotine seems to be moving in just the opposite direction. Additionally, the effects of nicotine are probably dose dependent or associated with the exposure duration and may be partly exerted by its receptors—nicotinic acetylcholine receptors (nAChRs). In this paper, we will mainly discuss the pathogenesis of AAAs involving inflammation, proteolysis, smooth muscle cell apoptosis and angiogenesis, and the roles of nicotine and nAChRs.